Causes of otitis media with effusion in children and specialist nursing interventions (儿童分泌性中耳炎原因分析及专科护理) - WANG Dongmei (王冬梅); GAO Mingyuan (高铭媛); ZHANG Li (张丽); WANG Xing (王星); HE Zihao (何子豪); ZHU Xinyu (朱鑫宇); XIAO Hong (肖红) (Journal of International Translational Medicine Limited, 2023)
By reviewing the studies on prevention and treatment of otitis media with effusion in children and experience of clinical practice, this article briefly analyzed the potential causes of otitis media with effusion in children, and specialist nursing interventions were provided for improvement of quality of otolaryngology specialist care. (通过文献检索结合专科护理防治特色, 浅析儿童分泌性中耳炎的原因, 总结专科护理措施, 为儿童分泌性中耳炎防治提供参考意见。)